Computational Mathematics, Numerical Analysis and Applications : Lecture Notes of the XVII 'Jacques-Louis Lions' Spanish-French School /: Lecture Notes of the XVII 'Jacques-Louis Lions' Spanish-French School. (2017) - Unknown
No abstract available